The practicality of popular scientific books about familia poaceae in mangrove swamps on Sungai Bakau to students' critical thinking ability - Giffaria Hafizha; Dharmono Dharmono; Atiek Winarti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
This development research aims to describe the popular scientific book Poaceae in the mangrove swamp of the Sungai Bakau Village on students' critical thinking skills. The stages of development include self-evaluation, expert test, individual test, small group test, and field test. The research subjects were five students for the response test and 3 observers for the implementation test of the popular scientific book Poaceae in the mangrove swamp of the Sungai Bakau Village on students' critical thinking skills. The type of data is descriptive data, using BIP implementation instruments and student responses are used for practicality of content and practicality of expectations. Technical data analysis was carried out in accordance with the objectives of the research which included the practicality of BIP. The calculation of the data is done by calculating the total score for each aspect tested and then dividing the total score so that the percentage that shows the practicality of BIP is obtained. The results showed that popular scientific books that had been developed were stated to be very practical based on the BIP individual test with an average of 89.74%. Popular scientific books are declared practical because the results of student responses with an average value of 90.74% with very good criteria, results of BIP implementation on average 92.80% with criteria strongly agree. Based on this, the developed BIP is very practical to use and makes it easier for students to learn.Abstrak Penelitian pengembangan ini bertujuan mendeskripsikan buku ilmiah populer Poaceae di rawa mangrove desa Sungai Bakau terhadap kemampuan berpikir kritis mahasiswa. Tahap-tahap pengembangan meliputi evaluasi diri, uji pakar, uji perorangan, uji kelompok kecil, dan uji lapangan. Subjek penelitian adalah lima mahasiswa untuk uji respon dan 3 observer untuk uji keterlaksanaan buku ilmiah populer Poaceae di rawa mangrove desa Sungai Bakau terhadap kemampuan berpikir kritis mahasiswa. Jenis data yaitu data deskriptif, menggunakan instrument instrument keterlaksanaan BIP dan respon mahasiswa digunakan untuk kepraktisan isi dan kepraktisan harapan. Teknis analisis data dilakukan sesuai dengan tujuan dari penelitian yang meliputi kepraktisan BIP. Perhitungan data dilakukan dengan cara menghitung jumlah skor tiap aspek yang diuji kemudian dibagi jumlah skor total sehingga didapatkanlah persentase yang menunjukan kepraktisan BIP. Hasil penelitian menunjukan buku ilmiah populer yang telah dikembangkan dinyatakan sangat praktis berdasarkan uji perorangan BIP dengan rata-rata 89,74%. Buku ilmiah populer dinyatakan praktis karena hasil respon mahasiswa dengan rata-rata nilai 90,74% dengan kriteria sangat baik, hasil keterlaksanaan BIP rata-rata 92,80% dengan kriteria sangat setuju. Berdasarkan hal tersebut BIP yang dikembangkan sangat praktis digunakan dan memudahkan mahasiswa dalam pembelajaran.